Signal-Space Projection Suppresses the tACS Artifact in EEG Recordings - Vosskuhl, Johannes; Mutanen, Tuomas P.; Neuling, Toralf; Ilmoniemi, Risto J.; Herrmann, Christoph S. (Frontiers in Human Neuroscience, 2020)
Background: To probe the functional role of brain oscillations, transcranial alternating current stimulation (tACS) has proven to be a useful neuroscientific tool. Because of the excessive tACS-caused artifact at the stimulation frequency in electroencephalography (EEG) signals, tACS+EEG studies have been mostly limited to compare brain activity between recordings before and after concurrent tACS. Critically, attempts to suppress the artifact in the data cannot assure that the entire artifact is removed while brain activity is preserved. The current study aims to evaluate the feasibility of specific artifact correction techniques to clean tACS-contaminated EEG data. New Method: In the first experiment, we used a phantom head to have full control over the signal to be analyzed. Driving pre-recorded human brain-oscillation signals through a dipolar current source within the phantom, we simultaneously applied tACS and compared the performance of different artifact-correction techniques: sine subtraction, template subtraction, and signal-space projection (SSP). In the second experiment, we combined tACS and EEG on one human subject to demonstrate the best-performing data-correction approach in a proof of principle. Results: The tACS artifact was highly attenuated by SSP in the phantom and the human EEG; thus, we were able to recover the amplitude and phase of the oscillatory activity. In the human experiment, event-related desynchronization could be restored after correcting the artifact. Comparison with existing methods: The best results were achieved with SSP, which outperformed sine subtraction and template subtraction. Conclusions: Our results demonstrate the feasibility of SSP by applying it to a phantom measurement with pre-recorded signal and one human tACS+EEG dataset. For a full validation of SSP more data is needed.